INDICATORS OF OXIDATIVE STRESS AND RESISTANCE OF ERYTHROCYTES IN PATIENTS WITH CHRONIC KIDNEY DISEASE STAGE VD DEPENDING ON MODALITY OF RENAL REPLACEMENT THERAPY - M. Kolesnyk; L. Korol; L. Migal; O. Burdeyna; V. Novakivskyy (Ukrainian Journal of Nephrology and Dialysis, 2015)
The object was to study the effect of oxidative factors and methods of renal replacement therapy (RRT) on indices of oxidative stress (OS) and resistance cells in blood in patients with chronic kidney disease stage V(CKD VD) and anemic syndrome.Material and methods. The study involved 47 patients with CKD VD: 14patients were treated by hemodiafiltration (HDF), 14 patients by hemodialysis (HD) and 19 patients by peritoneal dialysis (PD). The severity ofanemia was assessed according to the KDIGO (2012) criteria. The control group consisted of30 healthy people of the same age and sex. Along with the standard diagnostic methods, we defined the content of malonic dialdehyde in serum (MDAs) and in erythrocytes (MDAe), the content of ceruloplasmin (CPs), transferrin (TRs) and SH - groups in the blood serum, the index of the OS (IOS), catalase activity in serum (CTs), glucose - 6 - phosphate dehydrogenase (G - 6 - PDHe) and total peroxidase activity (TPA) in erythrocyte, osmotic (OR) and peroxide resistance (PR) of red blood cells and erythrocyte membrane permeability (EMP). Statistical analysis was performed using the programs Microsoft Excel 5,0 and MedStat.Results. It has been stated that in the CKD VD patients agains the rates in control group the MDAs content increased by 3.3 times and MDAe - 1.2 times, TRs content reduced by 34%, SH - groups - by 31%, TPAe - by 41% and G - 6 - FDGe - by 58%, marcers of OR by 30%, PR - by 60%; 4.6 times increased CTs activity and OSI; 2 times grew peroxide hemolysis (PH) and 1.3 times - EMP. The analysis (depending on the RRT modality) showed that the patients treated by HDF had typical MDAs increase by 3.9 times on a background of CPs by 24%o, TRs - 33%, SH - groups - 25%, TPAe - 51%, G6 - PDHe - 42%; the increase in serum OSI - 5.4 times and 2.6 times in erythrocytes, PR - by 3.6 times and CTs activity by 3,5 times; HD group were characterized by the highest value of MDAe, OSI, PH and CTs, along with more expressed decrease of indices TRs, SH - groups, TPA and G - 6 - FDHe activity compared with rates in patients with HDF. The patients treated with PD had the lowest content of MDAs and the highest values on the background ofTPAe, the significant increase of CPs by 1.7 times and lowest TRs and G - 6 - PDHe. The patients with PD showed twice lower OS activity by OSI.Conclusion.Thus, in patients with CKD VD, who had HD, HDF or PD an anemic syndrome was associated with high OS activity and the increased degree of hemolysis. These changes are stipulated by RRT methods: for patients receiving HDF were typical the lowest rates of hemolysis and the highest degree of protection for erythrocytes, and for patients treated with HD - the highest OS.